2012
DOI: 10.1371/journal.pone.0040292
|View full text |Cite
|
Sign up to set email alerts
|

GmcA Is a Putative Glucose-Methanol-Choline Oxidoreductase Required for the Induction of Asexual Development in Aspergillus nidulans

Abstract: Aspergillus nidulans asexual differentiation is induced by Upstream Developmental Activators (UDAs) that include the bZIP-type Transcription Factor (TF) FlbB. A 2D-PAGE/MS-MS-coupled screen for proteins differentially expressed in the presence and absence of FlbB identified 18 candidates. Most candidates belong to GO term classes involved in osmotic and/or oxidative stress response. Among these, we focused on GmcA, a putative glucose-methanol-choline oxidoreductase which is upregulated in a Δ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 61 publications
3
19
0
Order By: Relevance
“…The same effect was observed in null mutants of UDA genes such as flbE, flbD, and gmcA (Etxebeste et al 2012). Interestingly, the An4394 transcript was overexpressed in the DbrlA background ( Figure 7A, bottom).…”
Section: Global Analysis Of Flbb Activity In the Regulation Of Genes supporting
confidence: 62%
“…The same effect was observed in null mutants of UDA genes such as flbE, flbD, and gmcA (Etxebeste et al 2012). Interestingly, the An4394 transcript was overexpressed in the DbrlA background ( Figure 7A, bottom).…”
Section: Global Analysis Of Flbb Activity In the Regulation Of Genes supporting
confidence: 62%
“…These transporters may aid in regulation of ion and membrane potential homeostasis through their transport of nitrate, which is known to regulate the symbiosis (Vincill et al, 2005). These results indicated that GmcA is involved in a variety of metabolic processes, as has been described in A. niger and E. coli (Etxebeste et al, 2012;Liu et al, 2013).…”
Section: Discussionsupporting
confidence: 58%
“…The lower conidiation observed in Δ napA mutants might be related to their lower expression of gmcA gene (AN8547), encoding a putative glucose-methanol-choline oxidoreductase required for early stages of conidiophore development (Etxebeste et al, 2012). The fact that GmcA ortholog AFUA_3G01580 is also induced by H 2 O 2 in an AfYap1-dependent manner in A. fumigatus (Lessing et al, 2007) suggests that gmcA regulation by NapA is conserved, at least in the Aspergilli.…”
Section: Discussionmentioning
confidence: 99%